Dean Acheson and Fletcher Dean Robert Stewart with group of students - Unknown (Tufts Archival Research Center, 2007)
8x10; standing, left to right: Julien J. Hohenberg, Owen M. Quattlebaum, Douglas J. Bailey, David L. Larson, Thomas N. Bonsor. Sitting: Dean Acheson, Joyce R. Low, Helen T. Austern and Fletcher Dean Robert Stewart